Book Review Button, K.J. and Hensher, D.A. (eds.) Handbook of transport strategy, policy and institutions - Wee, Bert van (European Journal of Transport and Infrastructure Research, 2006)
They’ve done it again! Elsevier recently published the 6th Handbook for Transport, edited by Ken Button and David Hensher, the Handbook of Transport Strategy, Policy and Institutions. The handbook contains 834 pages, pleasantly split into 46 chapters of some 15-20 pages each (the perfect size for a train commuter with one hour in-vehicle time per one-way trip), and is organized into sections covering: • Institutional settings and markets • Planning perspectives • Asset management and funding • Regulatory issues • Evaluation frameworks • National studies Reviewing books is one of those jobs academics now and then do because it is more or less a moral task. It is very time consuming and does not result in any academic credits. The board of the European Journal of Transport and Infrastructure Research (EJTIR) was keen to publish a book review of this handbook. Unfortunately the first three persons we requested to do the job kindly suggested asking someone else, so I finally decided to do it myself, with, to be honest, a bit of hesitation.